Management Style and Employee Turnover in the Insurance Industry in Kenya - Gichungu, Teresia Wanjiku; Mukulu, Elegwa; Simiyu , Alice (Human Resource and Leadership Journal, 2024)
Purpose: To establish the influence of management style on employee turnover in the insurance industry in Kenya Methodology: The study applied descriptive explanatory research design. The target population was 404 senior staff drawn from 48 insurance companies in Kenya. The sample size for this study was 197 respondents determined using Krejcie and Morgan sample size determination formula. Stratified random sampling technique was used to select 197 managers. The study collected both primary and secondary data where questionnaires were used to collect primary data. The study carried out both descriptive and inferential analyses. Results from analysed data were presented in tables. Results: The results obtained from correlation analysis revealed a negative significant correlation between management style on employee turnover in the insurance industry in Kenya at p<0.05. The findings show that management style and employee turnover in the insurance industry in Kenya had a strong negative and significant relationship (r= -0.574, p<0.05). The relationship was considered significant since the p-value (0.000) was less than the selected level of significance (0.05). The model summary results show that the R-squared is 0.733 which suggests that 73.3% of all variation in employee turnover in the insurance industry in Kenya are explained by changes in management style. Unique contribution to theory, practice and policy: Maslow's (1943), hierarchy of needs theory used in this study may be used to anchor future studies on describing how employees' needs are placed into five progressive categories, beginning with basic physical needs and progressing up to needs for personal growth. The study recommends that the management of insurance companies should always involve staff in making organizations decisions and programs and ensures getting their approval in important matters before going ahead. According to the study, policy makers should formulate policies that will ensure that insurance companies embrace appropriate management styles.